Effect of itraconazole on pharmacokinetics of ZX-7101A tablets in healthy Chinese subjects - Wu, Junzhen; Wang, Yin; Liu, Wei; He, Jinjie; Wu, Jufang; Yu, Jicheng; Wu, Xiaojie; Su, Jianguang; Liu, Mei; Li, Yilin; Zhang, Jing (Frontiers in Pharmacology, 2025)
AimsA single-center, open label trial was conducted to evaluate the effects of itraconazole on the pharmacokinetics of ZX-7101A tablets in healthy Chinese adults.MethodsSubjects took a single dose of 40 mg ZX-7101A tablets on Day 1 on Day 31following once-daily itraconazole administration (200 mg, Days 26–50). The concentrations of ZX-7101A and ZX-7101 in plasma samples were determined by liquid chromatography–tandem mass spectrometry. Pharmacokinetic (PK) parameters of ZX-7101A and ZX-7101 were calculated, and the effects of itraconazole on the PK of ZX-7101 were evaluated.ResultsThe median Tmax of ZX-7101 was 4 h. In stage 1, the mean (±SD) Cmax, AUC0-t, AUC0-inf, and t1/2 of ZX-7101 were 90.86 ± 44.48 ng/mL, 6313.72 ± 1095.17 h*ng/mL, 6827.31 ± 1163.30 h*ng/mL, and 126.40 ± 28.88 h, respectively. In stage 2, the corresponding values were 117.63 ± 29.95 ng/mL, 9706.83 ± 1062.56 h*ng/mL, 10785.99 ± 1389.08 h*ng/mL, and 148.62 ± 28.72 h. Itraconazole increased ZX-7101 Cmax, AUC0-t, and AUC0-inf by 29.5%, 53.7%, and 58.0%, respectively, and prolonged t1/2 of ZX-7101 by 17.6%.ConclusionThe ZX-7101 exposure after coadministration with itraconazole is lower than the exposure after a single dose of 80 mg ZX-7101A tablets. It is therefore not necessary to adjust the dose of ZX-7101A 40 mg when coadministered with itraconazole.Trial registrationhttp://www.chinadrugtrials.org.cn, identifier: CTR20231556.